ALK3-SMAD1/5 Signaling Mediates the BMP2-Induced Decrease in PGE2 Production in Human Endometrial Stromal Cells and Decidual Stromal Cells - Zhang, Yu; Zhu, Hua; Chang, Hsun-Ming; Leung, Peter C. K. (Frontiers in Cell and Developmental Biology, 2020)
BMP2 is a critical factor that is involved in the processes of embryo implantation and uterine decidualization. The expression of cyclooxygenase (COX) and subsequent prostaglandin E2 (PGE2) production are critical for successful pregnancy. However, it is not clear whether BMP2 can regulate the production of PG during endometrial decidualization. The aim of this study was to investigate the effects of BMP2 on COX-1 expression and PGE2 production as well as the underlying molecular mechanisms in the human endometrium. Immortalized human endometrial stromal cells (HESCs) and human decidual stromal cells (HDSCs) were used as the study model to investigate the effects of BMP2-induced cellular activities. Our results showed that BMP2 treatment significantly decreased PGE2 production by downregulating COX-1 expression in both human endometrial stromal and decidual stromal cells. Additionally, BMP2 induced an increase in the levels of phosphorylated SMAD1/5/8, and this effect was completely abolished by the addition of the inhibitors DMH-1 and dorsomorphin, but not by SB431542. Knocking down ALK3 completely reversed the BMP2-induced downregulation of COX-1. Moreover, concomitantly knocking down SMAD1 and SMAD5 completely reversed the BMP2-induced downregulation of COX-1. Our results indicated that BMP2 decreased PGE2 production by downregulating COX-1 expression, most likely through the ALK3/SMAD1-SMAD5 signaling pathway in human endometrial stromal and human decidual stromal cells. These findings deepen our understanding of the functional role of BMP2 in the regulation of endometrial decidualization in humans.